2010
DOI: 10.1002/ar.21302
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes of the Epididymis and Description of the Excurrent Ducts of Phrynops geoffroanus (Testudines: Chelidae) During the Reproductive Cycle

Abstract: The seminal ducts (efferent ductule, epididymis, and deferent duct) in adults of Phrynops geoffroanus were examined using light microscopy. A series of tubules (efferent ductules) connect the testes to the epididymides. The efferent ductules are formed by a rete of small tubules of varying diameters, with simple columnar epithelium formed by the ciliated cells, nonciliated cells, and few basal cells. The epididymis is a simple, long and highly convoluted tubule that receives the efferent ductules throughout it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Alike to these species, the epididymal duct in T. scripta elegans was surrounded by smooth muscle tissue and loose connective tissue, the epithelium was composed of principal and basal cells, and the lumen was filled with spermatozoa. The heterogeneous shape of the principal cells and the location of the basal cells agreed with the findings described by Cabral et al (2011b) and with the description in Pelusios castaneus (Olukole et al 2014). In the present study, spermatozoa were found in the epididymal duct of all specimens analyzed, corroborating other studies (Viana et al 2013, Olukole et al 2014).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Alike to these species, the epididymal duct in T. scripta elegans was surrounded by smooth muscle tissue and loose connective tissue, the epithelium was composed of principal and basal cells, and the lumen was filled with spermatozoa. The heterogeneous shape of the principal cells and the location of the basal cells agreed with the findings described by Cabral et al (2011b) and with the description in Pelusios castaneus (Olukole et al 2014). In the present study, spermatozoa were found in the epididymal duct of all specimens analyzed, corroborating other studies (Viana et al 2013, Olukole et al 2014).…”
Section: Discussionsupporting
confidence: 90%
“…The histological morphology of the epididymis head in T. scripta elegans, with presence of ductuli efferentes and epididymal duct interspersed with connective tissue was similar to that of other turtles (Cabral et al 2011b, Viana et al 2013, Olukole et al 2014. The ductuli efferentes are responsible for the transport of spermatozoa from the testis to the epididymis, and present epithelium capable of reabsorbing more than 90% of the luminal fluid, increasing the concentration of spermatozoa entering the epididymis (Hansen et al 2004).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Histologically, the testes are formed by a series of seminiferous tubules with germ cells developing into sperm cells or spermatozoa. When the turtle reaches sexual maturity these sperm cells enter into a series of smaller ducts, known as the rete testis, which then move into the epididymal ducts, and then into the duct deferens towards the penis (Gribbins et al, 2003;Holmes and Gist, 2004;Pagliarini Cabral et al, 2011). On the other hand, the reproductive system of females is formed by a pair of ovaries, an oviduct, and the suspensory ligaments.…”
Section: Introductionmentioning
confidence: 99%